2012
DOI: 10.2214/ajr.10.6173
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MR Arthrographic Findings and Range of Shoulder Motions in Patients With Frozen Shoulder

Abstract: Coracohumeral ligament thickness on MR arthrography correlates with the range limitation of ER and IR in patients with frozen shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 33 publications
5
61
1
1
Order By: Relevance
“…This is in agreement with previous sonographic studies [2,9]. However, adhesive capsulitis was the dominant finding in some studies that examined hemiplegic shoulders with conventional arthrography [28], contrast enhanced MRI [26,27], and magnetic resonance arthrography [29]. This discrepancy between USS and other imaging techniques could potentially be addressed in future studies by combining all of the various sonographic methods of detecting adhesive capsulitis reported in English literature thus far [15,3034] in order to improve detection rate.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with previous sonographic studies [2,9]. However, adhesive capsulitis was the dominant finding in some studies that examined hemiplegic shoulders with conventional arthrography [28], contrast enhanced MRI [26,27], and magnetic resonance arthrography [29]. This discrepancy between USS and other imaging techniques could potentially be addressed in future studies by combining all of the various sonographic methods of detecting adhesive capsulitis reported in English literature thus far [15,3034] in order to improve detection rate.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the CHL thickness with a cutoff of 3 mm showed sensitivity of 51.28% and specificity of 91.43%, similar to those for adhesive capsulitis reported in several previous studies with cutoff values of 3 to 4 mm (sensitivity, 53%–83%; specificity, 85%–100%) . Hypoechoic changes at the rotator interval were also observed more frequently in patients with adhesive capsulitis than in the control group.…”
Section: Discussionsupporting
confidence: 89%
“…Thickening of the coracohumeral ligament and capsular thickening in the axillary recess are signs of capsulitis. 155,156 Coracohumeral ligament thickening in one study was significantly more prominent in patients with capsulitis and associated with limited external and internal rotation of the shoulder. 155…”
Section: Evaluating Instability and Dislocations Of The Shouldermentioning
confidence: 92%